The grey side of hibah amanah as inheritance instrument in Malaysia - Zul Kepli, Mohd Yazid; Ahmad Bustami, Tajul Aris (IIUM Press, International Islamic University Malaysia, 2019)
Hibah amanah has become a popular alternative to the Islamic system of inheritance (farā’iḍ) as it enables a donor to have full control during his life over his or her property while the beneficiary can only benefit from it upon the death of the donor. Hibah amanah enables the donor to circumvent the strict limitations provided under farā’id since the endowment of hibah amanah is arguably not subjected to farā’iḍ. This article starts with an analysis of the Sharī‘ah perspective of hibah amanah, focusing on the arguments forwarded by scholars that support and oppose hibah amanah, together with their justifications from the Qur’ān, Sunnah and other basis of their views (ijtihād). This qualitative study uses content analysis methodology and reveals that there are many legal complications and obstacles including the issue of Sharī‘ah-compliance, and the disputed permissibility of using Hibah amanah to circumvent farā’iḍ, the possibility of unfairness and bias, the denial of the beneficiaries’ rights without remedy, the threats from the money laundering perspective and the conflict between Shari’ah court and civil court over jurisdiction. This article stresses the importance of having a clear legal and regulatory mechanism to address all issues related to hibah amanah.